National development discourses within the global development hegemony : a case study of the post-2015 consultations in Tanzania - Maijala, Lotta (2014)
This study appears at a time when the new global post-2015 development agenda is being formed. In contrast to previous global development frameworks, we are now facing a universal agenda that sees development as a shared concern between the global North and South. Moreover, the new agenda is supposed to respond to many of the fallbacks of the Millenium Development Goals (MDGs), the lack of voice for ordinary people in particular.